Rivulet Flows And Flows Around Dry Patches On An Inclined Plane - Redwan, Nurul Ainina (2021)
This thesis presents a study on the thin-film flows of Newtonian and non-Newtonian power-law fluids on an inclined plane. Specifically, flow of slender rivulet and flow around slender dry patch are considered. The gravity or shear stress at the free surface drives the flow in the case of strong surfacetension effects.